Analyzing blockchain-based waste management investments in smart cities using quantum picture fuzzy rough modelling - Kou, Gang; Dinçer, Hasan; Pamucar, Dragan; Yüksel, Serhat; Simic, Vladimir (My University, 2025)
Blockchain-based waste management investments are key to increase the performance for achieving sustainable growth for both businesses and the country's economy. In this context, a new study should be conducted to identify the most important variables. Accordingly, the purpose of this study is to examine blockchain-based waste management investments via a novel model. The scope of this study is the smart cities that are defined as settlements that aim to improve the quality of life and ensure sustainability by using technology to manage and improve services. Firstly, artificial intelligence (AI) methodology is taken into consideration to compute the weights of the experts. Secondly, the weights of the criteria for blockchain-based waste management investments are computed. Finally, selected investment alternatives for smart cities are ranked with Vise Kriterijumska Optimizacija I Kompromisno Resenje (VIKOR) methodology. Additionally, a comparative analysis is also performed by technique for order preference by similarity (TOPSIS). In addition to this issue, a sensitivity analysis is also conducted with four different cases to check the coherency of the analysis results. The main contribution of this study is the calculation of the expert weights by AI. It is identified that participating in waste to energy schemes has the greatest significance. Similarly, optimizing the lifecycle management has also high weight. It is also defined that integration of physical and digital infrastructures is the most critical alternative. Moreover, urban innovativeness is another critical factor for this situation.
Keywords: Artificial Intelligence-Based Decision-Making; Blockchain-Based Waste Management; Energy Investments; Quantum Picture Fuzzy Rough Modelling